Converting Approach from Database Relational Schema into Horn Clauses Predicate Logic - Hussein, Bilal; Abdallah, Firas; Mehanna, Aref; Rabih, Yahia; Khawandi, Shadi (International Journal of Engineering and Technology, 2019)
The aim of this study is to build a transformation model capable to convert a database relational schema into a set of horn clauses predicate logic. Today, databases support trillion and trillion of data megabytes. They provide the main data sources for most of the decision-making systems. Now, organizations give more importance towards knowledge rather than information. But, knowledge cannot be extracted simply from databases. Usually, many complex procedures and techniques of data mining are required. Unlike databases, knowledge bases store knowledge (structured and unstructured information) in a computer-readable form. Moreover, the inference engine, supported by most of the knowledge bases, extracts new knowledge by simply implementing new rules. Based on Model Driven Architecture (MDA) approach and especially the modelsâ€™ transformation, this paper presents a set of mappings which transform a database (metadata and previous data) to knowledgebase expressed into facts and rules. A prototype transformation system is designed and implemented based on UML (Unified Modeling Language) class diagram and ATL (Atlas Transformation Language) which is the tool used for the model transformation. The prototype shows that the output of the transformation process can be operated directly by a logic programming language such as Prolog.Â Â